The Classification and Surgical Strategy of Intracardiac Leiomyomatosis - Hui-Li Gan; Jian-Qun Zhang; Ping Bo (Asian Journal of Surgery, 2009)
There is a great deal of heterogeneity in the surgical strategy to treat intracardiac leiomyomatosis (ICL), leading to a need to create a theoretical tool to clarify this situation. Methods: The data of 14 cases of ICL surgically treated in Anzhen Hospital from February 1995 to February 2009 were retrospectively reviewed. A system for classifying ICL was proposed based on four features of the lesion: size of intracardiac component; extent of inferior vena cava (IVC) involvement; venous pathway from uterus to IVC; and laterality of the lesion in the pelvis. The 14 cases of ICL were treated through multiple surgical strategies. Results: There were no operative deaths. The follow-up was 73.1 ± 59.2 months and one patient died from recurrence due to incomplete excision 5 months after the primary procedure. The 5-year survival rate calculated through Kaplan-Meier survival curve was 93.16 ± 4.98%. Of the surviving patients, 13 had ICL, 10 were in the New York Heart Association (NYHA) class I, and three were in NYHA class II. Conclusion: The surgical treatment of ICL can obtain a good mid- to long-term survival rate and satisfactory heart function, and the proposed classification system for ICL may be helpful to guide the selection of the surgical strategy for ICL, and may serve as the future basis for standardising the reporting of ICL management.